Application Of Geographic Information System And Hydrological Modelling Of Sungai Galas, Kelantan, Malaysia - Anees, Mohd Talha (2018)
Flooding is one of the natural hazard in the world as well as in Malaysia. Kelantan is also effected by flooding which need to be analysed. Flood analysis can be done through hydrological modelling by using high resolution data to find exact causes and effects of flooding. But in the absence high resolution or in situ data, what are the alternatives to conduct hydrological modelling? The objectives of this study were (i) to develop alternative methodologies and models for the generation of accurate flooding parameter’s values by using remote sensing and Geographic Information System (GIS) in a data sparse environment in Kelantan,